2020
DOI: 10.1021/acs.joc.0c00421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine-Promoted [3 + 2] Oxidative Cyclization for the Synthesis of Heteroarene-Fused [1,2,4] Thiadiazoles/Selenadiazoles

Abstract: Two new classes of heteroarene-fused [1,2,4]­thiadiazole and [1,2,4]­selenadiazole are synthesized through the iodine-mediated [3 + 2] oxidative cyclization of 2-aminoheteroarenes and isothiocyanates/isoselenocyanates. This oxidative [3 + 2] annulation strategy is highly regiospecific to proceed a selective C–N bond formation at the endo-nitrogen of 2-aminoheteroarenes followed by an intramolecular oxidative N–S/N–Se bond formation. It is the first example of an I2-mediated oxidative nitrogen–selenium (N–Se) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Scheme 14 Mechanistic studies 70 This result suggests that this reaction does not go through a radical pathway. Thus, a mechanism was proposed with isothiocyanates but can also be further applied with isoselenocyanates.…”
Section: Short Review Synthesismentioning
confidence: 98%
See 3 more Smart Citations
“…Scheme 14 Mechanistic studies 70 This result suggests that this reaction does not go through a radical pathway. Thus, a mechanism was proposed with isothiocyanates but can also be further applied with isoselenocyanates.…”
Section: Short Review Synthesismentioning
confidence: 98%
“…In an effort to develop an efficient method, Chen et al reported novel results on their metal-free synthesis of benzimidazole-fused [1,2,4]thiadiazoles from the reactions of 2-aminobenzimidazole and isothiocyanates (ITC), isoselenocyanates (ISC) and isocyanates. 70 Chen's group began with a study of the reaction conditions using 2-aminobenzimidazole (18a) (1.0 equiv) and phenyl isothiocyanate (19a) (2.0 equiv), with different oxidants (0.5-5.0 equiv), bases (3.0 equiv) and solvents over a range of temperatures in order to obtain the desired product, benzo [4,5]imidazo[2,1-c][1,2,4]thiadiazole 20aa (see Table 1). When molecular iodine (0.5 equiv) was introduced as the oxidant, along with K 2 CO 3 (3.0 equiv) as the base and chloroform as the solvent at reflux, the desired product 20aa was obtained in a 40% yield (Table 1, entry 1).…”
Section: Synthesis Of Heteroarene-fused [124]thiadiazoles/selenadiamentioning
confidence: 99%
See 2 more Smart Citations
“…These interactions increased partially the reactivities of substrates, thus triggering sequential reaction occur with a specific order. [31] Like NBS, molecular iodine can also assist some oxidative processes, such as the well-known Kornblum oxidation. [32] In view of these excellent performances, molecular iodine was quite often used by organic chemists as a kind of cheap and irreplaceable additive-like component to establish some catalytic systems.…”
Section: Molecular Iodinementioning
confidence: 99%